TIC application, improving competencies in first-year engineering students - Zamarreño-Bastías, Ricardo; Loyola-González, Natalia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The effectiveness of the joint application of the OVA and RA technological tools was evaluated in two Chemistry courses of the first year of engineering careers of two Chilean universities. The results obtained showed that the use of this technology was positive, since the statistical tests showed that 85.7% and 94.6% of the students of the evaluated universities improved their performance. Students in general do not know these tools to study, but they feel very comfortable in applying them when reviewing the contents covered in the Chemistry course.